Optical Singly-Ionized Iron Emission in Radio-Quiet and Relativistically Jetted Active Galactic Nuclei - Marziani Paola; Berton Marco; Panda Swayamtrupta; Bon Edi (MDPI, 2022)
The issue of the difference between optical and UV properties of radio-quiet and radio-loud (relativistically "jetted ") active galactic nuclei (AGN) is a long standing one, related to the fundamental question of why a minority of powerful AGN possess strong radio emission due to relativistic ejections. This paper examines a particular aspect: the singly-ionized iron emission in the spectral range 4400-5600 & ANGS;, where the prominent HI H beta and [Oiii]lambda lambda 4959,5007 lines are also observed. We present a detailed comparison of the relative intensity of Feii multiplets in the spectral types of the quasar main sequence where most jetted sources are found, and afterwards discuss radio-loud narrow-line Seyfert 1 (NLSy1) nuclei with gamma-ray detection and with prominent Feii emission. An Feii template based on I Zw 1 provides an accurate representation of the optical Feii emission for RQ and, with some caveats, also for RL sources. CLOUDY photoionization simulations indicate that the observed spectral energy distribution can account for the modest Feii emission observed in composite radio-loud spectra. However, spectral energy differences alone cannot account for the stronger Feii emission observed in radio-quiet sources, for similar physical parameters. As for RL NLSy1s, they do not seem to behave like other RL sources, likely because of their different physical properties, that could be ultimately associated with a higher Eddington ratio.